The Impact of Cultural Value Bias on Conscious Decision-Making in Counseling - Citta Lena Putri Mulyana; Nandang Budiman; Nadia Aulia Nadhirah (Suluh: Jurnal Bimbingan dan Konseling, 2024)
Counseling is an interactive process carried out by a counselor or guidance counselor with a counselee, with the aim of helping counselees understand themselves, overcome problems and develop their inner potential. Cultural values in counseling, highlighting their influence on the counselee's decision-making process. The impact of cultural value bias in counseling sessions is detailed, stressing the risk of misinterpretation, inappropriate evaluation, and even discrimination. The impact of cultural value bias on counselee decision-making in counseling is an important factor that influences the effectiveness of counseling sessions. Efforts that can be made to avoid cultural value bias include awareness, self-reflection, multicultural approaches, and collaboration with resources, as well as counselee involvement to increase understanding. counselors in dealing with cultural diversity. This research uses the Systematic Literature Review (SLRI) method to determine the impact of cultural value bias on counselee decision making in counseling. The importance of cross-cultural counseling is conveyed, that inclusive cultural values can improve counseling relationships, reduce bias, and increase effectiveness helping clients from diverse cultural backgrounds. By understanding cultural values and implementing appropriate strategies, counselors can create a counseling environment that is more responsive, inclusive, and supportive of clients from diverse cultural backgrounds.